Pengembangan Wilayah Pesisir Pantai Utara Jawa Tengah Berdasarkan Infrastruktur Daerah: Studi Kasus Kabupaten Jepara - Kurniawati Hapsari Ekosafitri; Ernan Rustiadi; Fredinan Yulianda (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2017)
Regencies in the northern coast of Central Java must transform their development priorities, based on their local potential resources and optimize their new sources of growth. Jepara, a costal regency located in northern coast of Central Java province, has a coastline of 82.73 km and 16 sub-districts consisting 9 coastal sub-districts and 7 inland sub-districts. The concentration of population in coastal areas causes the coastal sub-districts to be more developed than the inland sub-districts. The objectives of this study were (1) to analyze the level of sub-districts’ development based on their infrastructures and facilities and (2) to analyze stakeholder perception on coastal area development of Jepara. The methods used for analysis were scalogram analysis method and AHP (Analytical Hierarchy Process). The result of study showed that Kedung, Jepara, Keling and Karimunjawa sub-district are coastal sub-districts whith level I on hierarchy which means they are high development areas. The result of stakeholder perception analysis showed infrastructure availability as the main priority for coastal area development, nautical tourism as the main activity that shall be developed in coastal regions, and Karimunjawa sub-district as the main priority for development in Jepara regency.